2015
DOI: 10.1186/s12909-015-0344-z
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between participants’ level of education and engagement in their completion of the Understanding Dementia Massive Open Online Course

Abstract: BackgroundThe completion rates for Massive Open Online Courses (MOOCs) generally are low (5-10%) and have been reported to favour participants with higher (typically tertiary-level) education. Despite these factors, the flexible learning offered by a MOOC has the potential to provide an accessible educational environment for a broad spectrum of participants. In this regard, the Wicking Dementia Research and Education Centre has developed a MOOC on dementia that is evidence-based and intended to address this em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
110
1
12

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(134 citation statements)
references
References 21 publications
8
110
1
12
Order By: Relevance
“…In MOOCs, large number of learners may lead to a learner-driven learning ecosystem where group intelligence might become part of knowledge source. 16 In this study, most participates revealed the MOOC was useful toward their professional works. As shown in Table 1, certificate earners tend to think the most effective learning outcome camefrom short videos and in-video quizzes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In MOOCs, large number of learners may lead to a learner-driven learning ecosystem where group intelligence might become part of knowledge source. 16 In this study, most participates revealed the MOOC was useful toward their professional works. As shown in Table 1, certificate earners tend to think the most effective learning outcome camefrom short videos and in-video quizzes.…”
Section: Discussionmentioning
confidence: 99%
“…15 A research had shown that well-design discussion activities could raise the participation rate of a MOOC. 16 There are about 20 thousands registered pharmacists in Taiwan. By law, every registered pharmacist is required 150 continue education credits in 6 years.…”
Section: Introductionmentioning
confidence: 99%
“…Few universities of medicine used this kind of teaching [3,4,13,[15][16][17]. A high completion rate (38%) was observed in an Australian MOOC about dementia; 4409 registrants took part to the discussion boards, and 3624 completed the course [18]. However, a…”
Section: Discussionmentioning
confidence: 99%
“…In MOOCs, completion rates may differ by students' level of prior educational attainment (Pursel, Zhang, Jablokow, Choi, & Velegol, 2016), but this is not always the case (Goldberg et al, 2015). Currently, there is a great deal of interest in identifying quantifiable predictors of student retention and engagement as a means to intervene early in both traditional and online educational settings.…”
Section: Optimizing Engagement and Learning In Online Coursesmentioning
confidence: 99%